Light Building Constructions Based on Modified Gypsum Mixture Water Resistance and Water Performance - Xakimovna, Xamrayeva Luiza; N, Sharafutdinov M (European Journal of Life Safety and Stability (2660-9630), 2022)
Technical requirements for waterproof gypsum and anhydrite binder, lightweight construction constructor based on mixtures.